الإعلام الإساممي المعاصر من منظور مقاصدي دراسة تطبيقية عللى قناة الرسالة الفضائية - Jasim, Karam Mudhafar
Islam is a universal message which needs an appropriate media that carries Islam’s characteristics, goals and objectives. Islamic media aims to spread Islam and to address issues that affect people's lives. The problem is that there is a current dire need to employ the objectives of Islamic objectives in the contemporary media, to govern priorities, highlight the inclusion, achieve balance, and determine the methodology which can have influences upon reality. Neglecting these objectives means by media, will be random and unfruitful. The study aims to employ the Islamic objectives in the contemporary Islamic media, diagnose the regulations and instructions of the Islamic Media and analyze the relationship between contemporary Islamic media and the Islamic objectives. The study aimed at diagnosing the concept of Islamic media, and Islamic law's objectives. Finally, the present study evaluated Al-Resalah's channel programs. Through the adoption of; Inductive, and descriptive analytical methods. The findings revealed that: the existence of relationship between the Islamic media and the Islamic objectives; including the systematic, controls and objectives on which the theory of Islamic objectives media can be established. Moreover, it has been found that the contemporary Islamic media lacks inclusiveness and balance in Islamic Objectives in its messages directed to its recipient’s audience. Al-Karni’s program Hadathana Al-Zaman was found to be the best program in terms of inclusiveness. In a comprehensive analysis of all programs; the findings showed that within the most valued Islamic objectives, there is a balance in two of these objectives; Tawhid and Tazkya, whereas Al-Omran was neglected. However, within the necessary objectives; the focus was on the Islamic objective and (religion) while other objectives (progeny and money) were neglected. The study has recommended that the Islamic media accommodate the modern media movement and give attention to various areas of life when address audience.